Digitalization of Civil Transactions and Its Implications for Legal Certainty in the Era of Society 5.0 - Anita Mu’min; Muhammad Rafli Chaniago; Suartini (Yayasan Meira Visi Persada, 2025)
Digital transformation in the Indonesian civil law system is an inevitable necessity in line with the rapid development of information technology in the Society 5.0 era. One aspect that is directly affected is civil transactions, particularly in agreements and contracts that are now largely conducted electronically. This article aims to analyze the impact of the digitalization of civil transactions on legal certainty for the parties involved, as well as to evaluate the suitability of existing regulations, such as the Electronic Information and Transactions Law (ITE Law) and the Civil Code, in addressing this dynamic. By using a normative juridical approach and comparative analysis of legal practices in several countries, this article finds that although Indonesian regulations have begun to recognize the validity of electronic transactions, significant challenges still arise in the aspects of proof, authentication, and legal protection of digital transactions. Therefore, a more comprehensive and integrative reform of civil law is needed to ensure the principle of legal certainty in the digital realm. This update must include the establishment of clear technical guidelines, as well as the strengthening of regulations that support the implementation of safe and legally valid digital transactions, in order to keep up with technological developments and protect the rights of parties in electronic transactions